ROLE OF ST SEGMENT RESOLUTION ALONE AND IN COMBINATION WITH THROMBOLYSIS IN MYOCARDIAL INFARCTION (TIMI) FLOW IN PRIMARY PERCUTANEOUS CORONARY INTERVENTION FOR ST SEGMENT ELEVATION MYOCARDIAL INFARCTION - KHAN , N; ULLAH , A; ULLAH , R; IQBAL, U; MAGSI , M (Biological and Clinical Sciences Research Journal, 2023)
This study aimed to assess the effect of ST-segment resolution (STR) alone and in combination with TIMI flow after primary percutaneous coronary intervention (PPCI) for ST-segment elevation myocardial infarction (STEMI). The study was conducted at the Department of Cardiology, Peshawar Institute of Cardiology, Hayatabad Peshawar, KPK, from August 2022 to July 2023. Ninety patients with acute myocardial infarction were enrolled, and STR was considered successful if it reached 50% or complete STR (ST-segment back to the equipotential line). TIMI flow was evaluated after PPCI, and the primary outcome was two-year all-cause mortality. Results showed that each STR <50%, STR ≥50%, and complete STR occurred in 33.3% of the patients. Successful STR was the only independent predictor of 2-year death among all clinical factors. Combining TIMI flow and STR showed different 2-year mortality rates in subgroups; the lowest was seen in successful STR and TIMI 3 flow, the middle when either of these measures was decreased, and the greatest when both were abnormal. The study concluded that analyzing both STR and TIMI flow provides additional prognostic information beyond what either measure could provide. Therefore, it can be used as a reliable and convenient surrogate endpoint for determining successful PPCI. Additionally, the study found that post-PPCI STR is a strong long-term prognosticator for ST-segment elevation myocardial infarction.